Reconceptualizing Literary Theory Pedagogy: Bridging Abstract Epistemology and Contextual Interpretation - Hasanah, Atiq Aqiqotul; Fatsah, Hassanuddin; Malik, Harto S.; Hinta, Ellyana (Randwick International of Education and Linguistics Science Journal, 2026)
This study investigates the gap between students’ conceptual understanding of literary theory and their ability to apply theoretical frameworks in textual analysis in higher education. The research was conducted among students enrolled in a literary theory course at Universitas Muhammadiyah Gorontalo. It aims to reconceptualize literary theory pedagogy by integrating interpretative practice, collaborative learning, and digital mediation. This study employed a qualitative classroom-based research design through the implementation of a Problem-Based Learning (PBL) model integrated with an e-learning platform. Data were collected through classroom observations, student discussion records, reflective writings, and analysis of students’ interpretative assignments. The findings indicate that conventional lecture-centered approaches tend to present literary theory as abstract and declarative knowledge, which results in fragmented theoretical understanding and limited metatheoretical awareness among students. When learning activities were reorganized around interpretative problems derived from literary texts, students began to engage with theory as an analytical tool rather than as a static conceptual system. Collaborative discussions and peer feedback encouraged dialogic interpretation, while digital learning platforms extended reflective engagement beyond classroom time and enabled students to revise their analytical arguments. The study shows that integrating Problem-Based Learning with e-learning environments fosters a more reflective and contextual learning process, transforming literary theory into a practical framework for critical interpretation in higher education.